Sacral window for the surgery of L5 neurofibroma: A technical note - Kaplan, Metin; Özveren, Mehmet Faik (Turkish Neurosurgical Society, 2007)
Objective: To describe a way to increase the exposure for L5-S1 neurofibroma extending to presacral area. Summary of Background Data: Since the neurofibromas of L5-S1 level generally extend to the extraforaminal and presacral area, their resection is difficult compared to other lumbar levels. Methods: A 46-year-old female presented with severe pain in her left leg. There was a mild motor power loss in her left ankle and toe at plantar and dorsiflexion, and a mild hypoesthesia in the posterior of the left foot and its base. Lumbar computed tomography and magnetic resonance imaging showed a mass in the left intervertebral foramen extending to the extraforaminal presacral area at the level of L5-S1. The tumor was removed through a surgical bone window in the base of the sacrum and resection of L5 transverse process on the left side. Result: The tumor was removed totally. Following surgery, the patient's pain had totally disappeared and there was no alteration in her neurological status. Conclusion: L5-S1 neurofibroma was totally resected through a surgical window in the base of the sacrum.
Keywords: Neurofibroma; Sacrum; Surgical approach